Preliminary Reflexion on Basic Principle of Infrastructure Asset Management - Suprayitno, Hitapriya; Aryani Soemitro, Ria Asih (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2018)
Infrastructure is vital for regions life, mean while the infrastructure is always onerous and complex. The region must be able to manage its infrastructure well. Therefore the Basic Principle of Infrastructure Asset Management need to be well defined. This paper presents the result of an attempt to define the Basic Principle Infrastructure Asset Management. The Infrastructure Asset Management is defined as the science, the knowledge and the program to manage the infrastructure life in order to be able to well function in sustainable way, efficient and effective. The Infrastructure Asset Management knowledge consists of 7 basic knowledges, i.e on infrastructure, infrastructure function, infrastructure physical structure infrastructure externalities, infrastructure life cycle, infrastructure economy, and infrastructure managing organization. To master the Infrastructure Asset Management analyse tools must be added such as: statistics, decision making, risk management, quality management, strategic management, etc.